2017
DOI: 10.35808/ersj/854
|View full text |Cite
|
Sign up to set email alerts
|

Effective Marketing Strategy for Regional Banks

Abstract: The possibility of pursuing effective client policy in the context of marketing concept of the commercial bank's development strategy is considered. Hence, the goal of this study is to summarize the principles of effective client policy and offer solutions for the problems arisen while establishing the above. The general scientific methods of analysis and synthesis, economic-statistical methods and methods of abstract-logical judgments have been used. The article reveals the problems of establishing principles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Islam et al (2022) indicated that banks could gain more from event marketing than traditional advertising because the former could generate more attention than the latter. Simultaneously, Uksumenko et al (2017) asserted that banks needed to adapt themselves to the fast changes and made use of digital marketing services such as Internet banking, mobile banking, and ATM, to connect their customers, which could help banks promote their products effectively and reach their marketing goals (Nguru et al 2017).…”
Section: Marketing Strategymentioning
confidence: 99%
See 1 more Smart Citation
“…Islam et al (2022) indicated that banks could gain more from event marketing than traditional advertising because the former could generate more attention than the latter. Simultaneously, Uksumenko et al (2017) asserted that banks needed to adapt themselves to the fast changes and made use of digital marketing services such as Internet banking, mobile banking, and ATM, to connect their customers, which could help banks promote their products effectively and reach their marketing goals (Nguru et al 2017).…”
Section: Marketing Strategymentioning
confidence: 99%
“…Pursuing effective client policy in the context of marketing concept of the commercial bank's development strategy should be considered (Uksumenko et al 2017).…”
mentioning
confidence: 99%